2020
DOI: 10.3390/chemosensors8040098
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Factor for Quantifying Proteins in Unmodified Gold Nanoparticles-Based Aptasensing: The Effect of pH

Abstract: Unmodified gold nanoparticles (AuNPs)-based aptasensing (uGA) assay has been widely implemented in the determination of many different targets, but there are few reports on protein detection using uGA. Here, we designed a uGA assay for protein detection including the elimination of interfering proteins. Positively charged protein can be absorbed directly on the surface of AuNPs to form “protein corona”, which results in the aggregation of AuNPs even without salt addition, thereby preventing target protein dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Similar protective observations of proteins in culture media against the aggregation of the Au NPs were shown by Casals et al 22 where PC corona formation was found to be dependent on the size and surface chemistry of Au NPs. Recently, Lu et al 57 observed an influence of the pH of the media in relation to the isoelectric point of the protein on the aggregation of Au NPs following PC formation indicated by LSPR changes observed by UV/vis spectrophotometry. Interestingly, aspherical Au NPs such as Au nanorods (NRs) have two LSPR bands, transversal and longitudinal LSPR bands, that can be tuned on a wider wavelength scale.…”
Section: K Pmentioning
confidence: 99%
“…Similar protective observations of proteins in culture media against the aggregation of the Au NPs were shown by Casals et al 22 where PC corona formation was found to be dependent on the size and surface chemistry of Au NPs. Recently, Lu et al 57 observed an influence of the pH of the media in relation to the isoelectric point of the protein on the aggregation of Au NPs following PC formation indicated by LSPR changes observed by UV/vis spectrophotometry. Interestingly, aspherical Au NPs such as Au nanorods (NRs) have two LSPR bands, transversal and longitudinal LSPR bands, that can be tuned on a wider wavelength scale.…”
Section: K Pmentioning
confidence: 99%
“…To simplify the detection procedure, colorimetric sensors based on the nanoparticles have attracted considerable attention due to their instant, low-cost, and visual identification characteristics [6,7]. For example, Joshi et al reported a sensitive and selective colorimetric probe for Al 3+ by using indole-2-carboxylic acid capped sliver nanoparticles (AgNPs) [8].…”
Section: Introductionmentioning
confidence: 99%